Polychlorinated dibenzo-dioxins and polychlorinated dibenzo-furans exposure and altered lung function: The mediating role of oxidative stress. (April 2020) - Zhang, Zhuang; Zhou, Min; He, Jintong; Shi, Tingming; Zhang, Sukun; Tang, Naijun; Chen, Weihong
Graphical abstract: Highlights: The FVC and FEV1 levels were inversely correlated with PCDD/Fs exposure levels. Urinary 8-OHdG levels were inversely correlated with lung function parameters. Urinary 8-OHdG mediated the associations of PCDD/Fs exposure with FVC levels. Urinary 8-OHdG mediated the associations of serum PCDD/Fs with FVC and FEV1 levels. Abstract: The lung has been reported to be one of the target organs of polychlorinated dibenzo-dioxins and polychlorinated dibenzo-furans (PCDD/Fs) in many toxicological studies. While the associations between PCDD/Fs exposure and lung function levels have not been investigated thoroughly. This study aimed to explore these associations and the potential mediating role of oxidative stress. In this study, 201 foundry workers and 222 non-exposed general residents were recruited from central China, and their lung function parameters were measured. Air and food samples were collected to determine the PCDD/Fs levels for individual PCDD/Fs exposure estimation. Serum PCDD/Fs levels were determined in a subgroup of individuals randomly selected from the study population to reflect the body burden. It was found that each 1-unit increase in ln-transformed concentration of PCDD/Fs exposure (fg TEQ/bw/day) was associated with a 0.47 L decrease in FVC and a 0.25 L decrease in FEV1 . Each 1-unit increase in ln-transformed concentration of serum PCDD/Fs (fg TEQ/g lipid) was associated with a 0.36 L decrease in FVC and a 0.24 L decrease in FEV1 . Urinary 8-hydroxy-2′-deoxyguanosine (8-OHdG) was not only positively related to PCDD/Fs exposure, but also inversely associated with FVC and FEV1 are FVC (β = −0.15, 95% CI: −0.22 to −0.08) and FEV1 (β = −0.07, 95% CI: −0.13 to −0.02). Mediation analysis revealed that urinary 8-OHdG mediated 12.22% of the associations of external PCDD/Fs exposure with FVC levels, 28.61% and 27.87% of the associations of serum PCDD/Fs with FVC and FEV1 levels respectively. Our findings suggested that PCDD/Fs exposure was associated with decreased lung function levels by a mechanism partly involving oxidatively generated damage to DNA.